The State Visits of Edward VII - Glencross, Matthew. author. aut Link
IX, 230 p.
Keywords: This book explores the revival under Edward VII of the ceremonial state visit by British monarchs, showing the impact and importance of active royal diplomacy during his reign. Using the Royal Archives, memoirs and newspapers, it reveals the contribution made by the use of ceremony and public display to popular appreciation of the monarchy.